2018
DOI: 10.1021/acsanm.8b01799
|View full text |Cite
|
Sign up to set email alerts
|

A Reduced Graphene Oxide Quantum Dot-Based Adsorbent for Efficiently Binding with Organic Pollutants

Abstract: This paper, for the first time, presents a novel, robust, and efficient high-quality reduced graphene oxide quantum dot (GQD)-based adsorbent for addressing the alarming environmental pollution issues nowadays. Such GQDs were fabricated in a facile manner via a combined green chemistry (GC) and temperature-controlled sonication irradiation (TSI) process. The mechanism underlying the fragmentation of the reduced graphene oxide (RGO) sheets prepared by GC with vitamin C (VC) as the only reactant to regulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 74 publications
2
14
0
Order By: Relevance
“…Conversely, the average number of the viable bacteria cells on the standard control test specimen in the absence of the ES PLA/TiO 2 fibers was dramatically increased after the 24 h of visible light irradiation, likely because bacterial proliferation readily proceeded without the inhibition effect from the destructive reactive oxygen species generated by the photocatalytic reactions over the PLA/TiO 2 fibers. As a result, the as-prepared PLA/TiO 2 fibers can find promising antimicrobial applications by considering its high antibacterial efficiency, as well as its robust and portable merits that cannot be obtained in the traditional powdery samples [34,35,36,37,38,39,40,41,42,43,44,45,46]. R 1 = (( N 0 – N 24h )/ N 0 ) × 100…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the average number of the viable bacteria cells on the standard control test specimen in the absence of the ES PLA/TiO 2 fibers was dramatically increased after the 24 h of visible light irradiation, likely because bacterial proliferation readily proceeded without the inhibition effect from the destructive reactive oxygen species generated by the photocatalytic reactions over the PLA/TiO 2 fibers. As a result, the as-prepared PLA/TiO 2 fibers can find promising antimicrobial applications by considering its high antibacterial efficiency, as well as its robust and portable merits that cannot be obtained in the traditional powdery samples [34,35,36,37,38,39,40,41,42,43,44,45,46]. R 1 = (( N 0 – N 24h )/ N 0 ) × 100…”
Section: Resultsmentioning
confidence: 99%
“…The degree of oxidation is around 40% as measured by x-ray photoelectron spectroscopy (XPS) analysis (figure S3). The oxidized functions include approximately C-OH 284 eV, C=O 288 eV, O=C-OH 291 eV [42]. Milli-Q water (Q-Gard 00D2) with a resistivity above 18.2 MΩ cm at 25°C and 2-Propanol (IPA) absolute 99.9% were purchased from Sigma Aldrich and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…Many researchers have reported that the oxygen-containing functional groups of CNDs are responsible for their interesting optical properties such as strong excitation-dependent photoluminescence (PL). However, the specific role of oxygen in CNDs has not yet been fully elucidated because it is still difficult to prepare oxygen-less CNDs via conventional synthetic methods for comparative analysis in terms of the oxygen content. Although CNDs subjected to post-synthetic reduction have a lower oxygen content, they still contain a significant amount of oxygen. Furthermore, the oxygen-containing groups generally render CNDs to be strongly hydrophilic. While this is advantageous in many applications such as in biomedicine, it could hinder applications that require the use of hydrophobic solvents.…”
Section: Introductionmentioning
confidence: 99%